Effectiveness of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence in Cases of Gender-Based Violence - Salsabilla, Azra; Sumanto, Listyowati (CV. Rayyan Dwi Bharata, 2024)
Gender-based violence is a social phenomenon that has existed since ancient times and has become increasingly prevalent lately. In fact, gender-based violence is increasing, both in terms of number, form and modus operandi which are increasingly diverse. The Law on the Crime of Sexual Violence is considered to still require more nuances in the definition and details of sexual violence, does not provide a guarantee of safety and protection for victims and also does not fully consider an adequate gender perspective. The research method uses a descriptive normative legal research type, and the data is analyzed qualitatively. Drawing conclusions uses deductive logic. The purpose of the study is to describe the effectiveness of the Law on the Crime of Sexual Violence against cases of gender-based violence. The results of the study indicate that the existence of the Law on the Crime of Sexual Violence is still not fully effective because it is seen from the increasing cases of gender-based violence every year. It is recommended that there needs to be a strong commitment from law enforcement to consistently apply the rules of the Law on the Crime of Sexual Violence to support the effectiveness of the Law on the Crime of Sexual Violence.